Bio-Cementation of Sandy Soil through Bacterial Processing to Precipitate Carbonate - Shannoon, Layth K.; Ibrahim, Mohammad A. (Al-Nahrain Journal for Engineering Sciences, 2020)
Bio-cement built on microbial induced carbonate precipitation MICP, be able to consolidate the loose grains and can applied for soil reinforcement. In this study, the performing of an ureolytic Sporosarcina Pasteurii for sand stabilization was estimated. The S. Pasteurii Could effectively consolidates sand particles through urea hydrolysis and the successive production of calcite. The bio improved sands had relative great compressive strength after 60 days exposure to bacterial cells injections cycles. The compressive strength of bio stabilized sands was reliant on the utilized cell concentrations and density of urea and CaCl2. High bacteria cell masses decreased the compressive strength. The optimal density of cell, was OD600 0.5, when cost and performance were taken into account. The study shows that bio cementation of sand built on microbial induced carbonate precipitation (MICP) has ability for the reduction of sand permeability through pore clogging with precipitated carbonate.